Heterostructured graphene oxide membranes with tunable water-capture coatings for highly selective water permeation. Issue 12 (8th March 2021) - Zhang, Zhiming; Wu, Hong; Li, Ying; Liu, Yue; Cao, Chenliang; Wang, Hongjian; Wang, Meidi; Pan, Fusheng; Jiang, Zhongyi
Abstract : Heterostructured graphene oxide membranes with water-capture tannic acid coatings were constructed for highly selective water permeation. Abstract : Graphene oxide (GO) laminar membranes with fast water-transport nanochannels hold great promise for water-selective molecular separations, but the water-capture ability of membrane surfaces limits the separation performance. Herein, we engineered water-capture coatings on GO laminar membranes using structurally tunable tannic acid (TA) nanoaggregates as building blocks via a bottom-up method, acquiring heterostructured GO membranes for alcohol dehydration. The abundant oxygenated functional groups of TA coatings captured water from alcohol aqueous solutions and enhanced the surface water-capture capacity by up to 309%. We manipulated the surface water-capture ability by regulating the aggregation structure and the subsequent assembly process of the TA nanoaggregates. By virtue of the synergistic effect of the enhanced surface water-capture ability and fast water-transport GO nanochannels, the optimized heterostructured GO membrane exhibited high permeation flux of 9988 g m −2 h −1 and a superior separation factor of 4424 for n -butanol dehydration. This study provides a novel avenue to high-performance GO membranes with rationally designed heterostructures.